2011
DOI: 10.1016/j.jhep.2010.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoplasmic calcium regulates cell proliferation through legumain

Abstract: Background and Aims Nucleoplasmic Ca2+ regulates cell growth in the liver, but the proteins through which this occurs are unknown. Methods We used Rapid Subtraction Hybridization (RaSH) to subtract genes in SKHep1 liver cells expressing the Ca2+ buffer protein parvalbumin (PV) targeted to the nucleus, from genes in cells expressing a mutated form of nuclear-targeted PV which has one of two Ca2+-binding site inactivated. The subtraction permitted selection of genes whose expression was affected by a small alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 44 publications
3
46
0
Order By: Relevance
“…In comparison to the limited variety of biochemical cleavage mechanisms, there is an impressively diverse cellular and extracellular repertoire of physiological substrates, as well as endogenous protease inhibitors which are called into action for the regulation of proteolysis in response to cellular conditions (Andrade et al 2011;Brix et al 2013;Dauth et al 2011a;Turk et al 2008). Locally and temporally controlled protease activities are already seen very early in life, such as the acrosomal process during fertilization of the egg cell (Mao and Yang 2013).…”
Section: The Protease Family Businessmentioning
confidence: 99%
“…In comparison to the limited variety of biochemical cleavage mechanisms, there is an impressively diverse cellular and extracellular repertoire of physiological substrates, as well as endogenous protease inhibitors which are called into action for the regulation of proteolysis in response to cellular conditions (Andrade et al 2011;Brix et al 2013;Dauth et al 2011a;Turk et al 2008). Locally and temporally controlled protease activities are already seen very early in life, such as the acrosomal process during fertilization of the egg cell (Mao and Yang 2013).…”
Section: The Protease Family Businessmentioning
confidence: 99%
“…Processing of AEP requires sequential removal of the C-and N-terminal propeptides at different pH thresholds to generate 46-kDa (active pro-AEP) and 36-kDa (active AEP) active enzymes (8,9). AEP has multiple roles depending on substrate specificity such as initiator of invariant chain processing during MHC class IImediated antigen presentation (10), inducer of cell migration (11,12), and modulator of processes such as proliferation (13) and both pro-death and pro-survival functions using apoptotic mechanisms (14). The variety of roles of AEP is due to its ability to proteolyse multiple substrates, including among others the extracellular matrix protein fibronectin (15), progelatinase (16), and cathepsin H, B, and L (17).…”
mentioning
confidence: 99%
“…9,10 Moreover, some studies have reported that AEP was related to tumor cell proliferation. 8,23 And blocking of AEP with antibody was reported to inhibit tumor progression and metastasis. Once AEP combined with its substrate recognition, it could be upregulated in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it is reported that AEP is highly expressed in many solid tumors, such as hepatocellular cancer, gastric cancer, breast cancer, colorectal cancer and lung cancer. [8][9][10][11][12][13] However, the mechanism of AEP in epithelial ovarian cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%